Un nuevo existencialismo para tiempos transhumanos - Binetti, María José (Sapientia, 2023)
Philosophical thought in recent decades has been dominated by socio-constructivism in its two linguistic and materialist versions. The result was the progressive deconstruction and dissemination of reality in general and of human existence in particular. The subject then became a post-subject, the body became construct, knowledge sank into post-truth micro-narratives, sexual difference into a post-gender imaginary, and the human person became a transhuman cyborg. The conclusion is an anti-humanist culture operated by the power apparatus of the globalist establishment. In the context of this spiritual bankruptcy, a task of humanist and existential restoration is urgently needed. The current article will follow a brief historical-conceptual journey through socio-constructivism and its post-gender and transhuman outcome, along with the alternative of a neoexistential realism based on the spiritual dignity of the human being.